The Study of Text from Discourse Analysis Perspectives: Theory and Practice - FETHIZA TEDJANI, Mouna (My University, 2015)
The present enquiry explores insights of analysis discourse in the study of text focusing on its contextual, macro-organisational and cohesive level. We propose discourse analysis model as it examines text at the three-sided stated levels: schematic knowledge, macro-organization, and cohesion respectively as this triangular focus is a solution to the failure of contemporary teaching practices of foreign language (hereafter FL) that focus more on systematic knowledge neglecting the areas of language. The aim of this investigation is to exploit findings of discourse analysis in FL classroom in general and text creation in particular, suggesting teaching procedures, activities, and varieties of texts to educators and researchers.
Keywords: Keywords: Discourse Analysis, text, Foreign language Schematic knowledge Macroorganization, Cohesion.